Validation of a Scale to Assess Patients' Comprehension of Frequently Used Cardiology Terminology: The Cardiac TERM Scale in Brazilian Portuguese - De Melo Ghisi G.L. (2019)
© 2018 by the Association of Rehabilitation Nurses.Purpose The aim of this study was to psychometrically validate the translation of a questionnaire on patient understanding of cardiology terminology (TERM) to Brazilian Portuguese. Design After piloting the translation and cross-cultural adaptation, the 16-item TERM questionnaire was psychometrically tested. Methods Internal and test-retest reliability, as well as validity, were assessed in 322 cardiac patients. Findings Internal (α =.88) and test-retest reliability (all weighted Kappa > 0.63) exceeded the minimum recommended standards. Criterion validity was supported by significant differences in mean scores by socioeconomic indicators (p <.01). Discriminant validity was supported in that cardiac rehabilitation participants had significantly higher TERM scores (p <.001). Participants did not correctly define any of the terms, and a floor effect was identified in all terms. Conclusions The Cardiac TERM Scale was demonstrated to have good reliability and validity. Clinical Relevance The scale can be used by healthcare professionals, such as nurses. Results can be used to inform patient education, which could in turn impact patient adherence to medical advice and hence outcomes.